2022
DOI: 10.1136/jim-2021-002159
|View full text |Cite
|
Sign up to set email alerts
|

Sequential administration of pemetrexed and cisplatin reprograms tumor immune microenvironment and potentiates PD-1/PD-L1 treatment in a lung cancer model

Abstract: This article aimed to investigate the effects of the administration method of pemetrexed and cisplatin on the efficacy and safety of treating non-small cell lung cancer (NSCLC) and the intrinsic molecular mechanism. Subcutaneous injection of A549 cells into BALB/C nude mice was used to explore the efficacy of different administration methods of pemetrexed and cisplatin in vivo. Immunogenic cell death (ICD) was evaluated by ATP secretion, ecto-CALR expression, and high mobility group protein 1 release. Western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…For one thing, TNF-α can inhibit tumors via activating programmed death cascades in targeted cells, with devastating efects on the function of lysosomal enzymes and/or lysosomal membrane integrity. TNF-α signaling can also be used to induce B7-H1 and PD-L1 expression on CD8 + T cells via several pathways, thereby causing immune resistance [25][26][27]. We found that three diferent doses of aconite all increased TNF-α levels in the serum of tumor-bearing mice.…”
Section: Discussionmentioning
confidence: 75%
“…For one thing, TNF-α can inhibit tumors via activating programmed death cascades in targeted cells, with devastating efects on the function of lysosomal enzymes and/or lysosomal membrane integrity. TNF-α signaling can also be used to induce B7-H1 and PD-L1 expression on CD8 + T cells via several pathways, thereby causing immune resistance [25][26][27]. We found that three diferent doses of aconite all increased TNF-α levels in the serum of tumor-bearing mice.…”
Section: Discussionmentioning
confidence: 75%
“…To further clarify the specific molecular mechanism of B3GNT3 in lung adenocarcinoma cells, this study attempted to use a PD-L1 inhibitor to overexpress B3GNT3. As one of the PD-1 ligands, PD-L1 can be expressed constitutively in different tissues under physiological conditions ( 27 ), mainly in activated T lymphocytes, B lymphocytes, dendritic cells (DC), monocytes, mesenchymal stem cells (MSCs), bone marrow (BM)-derived mast cells and various immune privileged organs ( 28 , 29 ). However, in the tumor immune microenvironment, the PD-1/PD-L1 axis is hijacked by cancer cells to evade immune surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…They indicated that sequential treatment with pemetrexed and cisplatin induces activation of the STING pathway both in vivo and in vitro settings in NSCLC patients. This activation enhances the infiltration of CD8 + T cells and up-regulates the level of PD-L1, which provides a theoretical foundation for the development of clinical medication [ 102 ]. In the case of EGFR-TKI treatment failure, the combination of PEM and CD73 inhibitors can synergistically induce cancer cell STING and increase immunogenicity in TKI-resistant EGFR mutant lung cancer.…”
Section: The Latest Research Progress Of Sting In Nsclc Treatmentmentioning
confidence: 99%